A novel proof of an old result

-coquitaoFebruary 24, 2009

1

Since F n . In n order to attain this end.n We only need to show that the limit of the ratio sn = FF+1 exists. we'll prove that sn is a Cauchy sequence.

jsn+1   snj = Fn+2   FF+1 .

.

.

n+1 n .

Fn+2 Fn   F2 +1 .

n .

= .

.

Fn+1 Fn n+1 .

( 1) .

.

= .

Fn+1 Fn .

Hence. 1 = Fn+1 Fn ! 1 1 1 =   Fn 1 Fn Fn+1 1 1 1    Fn 1 Fn 2Fn 1 = 2Fn Fn 1 1 = jsn   sn 1 j. 2  n 1 1 it follows that jsn+1   sn j js2   s1j. for .

xed 2 p > 0 we have .

.

.

.

.

.

.

.

.

.

.

.

.

.

.

.

2 = j(sm+p   sm+p 1 ) + (sm+p 1   sm+p 2 ) + : : : + (sm+1   sm )j (   m 1 ) 1 m+p 2  1 m+p 3 1 + + ::: + js2   s1j 2 2 2  m 1 1 < 2 js2   s1j: 2 2 . m and any j m+p   mj s s  n The desired conclusion follows now from the fact that 1 3 0 as n 3 I.

Sign up to vote on this title
UsefulNot useful